Facet‐Dependent On‐Surface Reactions in the Growth of CdSe Nanoplatelets. Issue 49 (22nd October 2019) - Zhu, Chenqi; Chen, Dongdong; Cao, Weicheng; Lai, Runchen; Pu, Chaodan; Li, Jiongzhao; Kong, Xueqian; Peng, Xiaogang
Abstract: Facet‐dependent on‐surface reactions are systematically studied on zinc‐blende CdSe nanoplatelets with atomically‐flat {001} basal facets and small yet non‐polar side facets. The on‐surface half‐reactions between the surface Se sites and Cd carboxylates in the solution are qualitatively equivalent to those on the spheroidal counterparts. Conversely, the on‐surface half‐reactions between the surface Cd sites and the activated Se precursors in solution show a strong facet‐dependence, which includes three distinguishable stages. In the first stage, the Se precursors adsorb onto the small and non‐polar side facets of the nanoplatelets. The second stage is initiated by the adsorbed Se precursors at the side‐basal plane edges and proceeds from the edges to the center of the basal planes in quasi‐zeroth‐order kinetics. In the third stage, the nanoplatelets are dismantled, which includes the creation of a hole in the middle and a build‐up of thick edges. Abstract : Grow, little platelet : The on‐surface reactions of nanoplatelets between the surface Cd sites and activated Se precursors in the solution is found to be strongly facet‐dependent. The process occurs in two stages—rapid adsorption onto the non‐polar side facets and slow surface reaction on the polar {100} basal facets—as well as one destructive (ripening) stage.